(untitled) (Singapore,The Netherlands,Australia, 1998)
Contents: Southeast Asia, like other non-Western areas, has often been seen as economically static and self-sufficient until the arrival of late 19th century capitalism, for no better reason than lack of evidence to the contrary. This volume seeks to lay a basic for more solid analysis of the precolonial record through accumlating one type of data-exports-for which the record is long and continuous.
Keywords: Xuất khẩu,Exports; Lịch sử,History; Đông Nam Á,Southeast Asia